2021
DOI: 10.4103/aian.aian_183_20
|View full text |Cite
|
Sign up to set email alerts
|

Do Imaging Markers of Cerebral Small Vessel Disease Predict Hematoma Volume and Outcome in Acute Intracerebral Hemorrhage?

Abstract: Background and Purpose: Cerebral small vessel disease (CSVD) markers have not been widely studied in relation to hematoma volume and growth in hypertensive intracerebral hemorrhage (ICH). The objectives to assess the relationship of white matter hyperintense lesions (WMHL), microbleeds (MBs), and cortical siderosis (CSS) with hematoma volume, hematoma expansion (HE), and 3 months outcome in patients with hypertensive ICH. Methods: All consecutive acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…For decades, cSS has been proven to be a strong risk factor for unfavorable neurologic outcomes and is related to other clinical characteristics that correlate with worse outcomes, such as recurrent ICH and large hematoma (1,(3)(4)(5)(6)(7)(8). However, it is unclear whether the deleterious outcome is determined by cSS or by other potential factors induced by cSS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For decades, cSS has been proven to be a strong risk factor for unfavorable neurologic outcomes and is related to other clinical characteristics that correlate with worse outcomes, such as recurrent ICH and large hematoma (1,(3)(4)(5)(6)(7)(8). However, it is unclear whether the deleterious outcome is determined by cSS or by other potential factors induced by cSS.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear whether the deleterious outcome is determined by cSS or by other potential factors induced by cSS. We made the hypothesis that part of the effect (indirect effect) of cSS and 90-day mRS was mediated by hematoma volume based on the results of numerous cohort studies that concluded those as follows: (i) cSS is associated with large hematoma volume in patients with ICH; (ii) patients with cSS are more likely to have poor outcomes after ICH, including higher risk of recurrent ICH and poor functional recovery; and (iii) hematoma volume is the most significant factor deciding prognosis of ICH, and large hematoma volume leads to poor outcomes (1,(3)(4)(5)(6)(7)(8). Therefore, a probable relationship chain is that cSS leads to large hematoma volume and then caused poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, for the evaluation of WMH, in addition to using different sequences, such as T1‐weighted, T2‐weighted, and T2‐FLAIR, it is necessary to use the Fazekas scale, which is a standard for grading WMH on imaging. 12 , 13 It evaluates paraventricular and deep WMH separately and finally judges the WMH level according to the sum of the scores. Unfortunately, despite its significant impact, accurate diagnosis of CSVD remains a challenge due to variations in imaging protocols, inadequate quantitative metrics, and clinician bias.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional diagnosis of CSVD is based on a comprehensive evaluation of the typical MRI signs of CVSD to obtain the total load score and provide the corresponding clinical diagnosis decision, such as evaluating the degree of brain atrophy using T1‐weighted MRI images and counting vascular lacunar foci based on T1‐weighted MRI and T2‐fluid‐attenuated inversion recovery (FLAIR) images. Moreover, for the evaluation of WMH, in addition to using different sequences, such as T1‐weighted, T2‐weighted, and T2‐FLAIR, it is necessary to use the Fazekas scale, which is a standard for grading WMH on imaging 12,13 . It evaluates paraventricular and deep WMH separately and finally judges the WMH level according to the sum of the scores.…”
Section: Introductionmentioning
confidence: 99%